Inulin: A promising carrier for controlled and targeted drug delivery system - Akram, Wasim; Joshi, Ramakant; Garud, Navneet (Journal of Drug Delivery and Therapeutics, 2019)
The delivery of a drug to the preferred site of action is referred to as drug targeting. The benefits of drug targeting are a reproducible and controlled release rate of the therapeutic compound, which forestalls overdose. Due to the potential to treat colonic diseases with minimum side effects, colon targeting has become of high interest over the last decades. Inulin was investigated for its potential as encapsulation material regarding its enzymatic degradability and its drug release behaviour. Inulin is a polysaccharide with a widespread range of therapeutic uses such as a carrier in a drug delivery vehicle, as a diagnostic/analytical tool or as a dietary fibre with additional health benefits. In the main, much research has focused on inulin as a drug delivery carrier for colon-specific drug delivery. The justification for this is its potential to survive in the stomach’s acidic environment. This unique stability and strength are utilized in many ways to deliver drugs safely to the colon, where they can be easily absorbed through the gut epithelium into the blood. There are also some proofs that inulin’s prebiotic features also lead to health benefits, mainly for patients with inflammatory bowel disease or in the prevention of colonic cancer. Inulin based hydrodynamic research will be useful to discover the potential of inulin.